Pelatihan Pembuatan Virtual Tour bagi Kelompok Sadar Wisata Desa Sidatapa, Kabupaten Buleleng, Bali - Ni Made Ary Widiastini; Made Aristia Aristia Prayudi; Putu Indah Rahmawati; I Gede Rasben Dantes (Faculty of Cultural Sciences, 2020)
The presence of increasingly sophisticated information technology has implications for the emergence of various innovations and creativity, by utilizing the development of information technology. One that is growing rapidly during the pandemic is a virtual tour, as a substitute for a tour to a place directly, which is brought to a screen using either a laptop, PC or mobile phone. Sidatapa Village, as one of the tourist villages in Buleleng Regency, has recently developed tourism products, one of which is a tour to get to know the culture in the village, experiencing obstacles due to the social restrictions. Tourists cannot visit the village directly and get to know the culture in the ancient village. Seeing the trend of virtual tours that are well developed in Indonesia, in this community service program, tourism community group who act as tour guides are given virtual tour training. Sidatapa village is unique, namely as the village of Bali Aga and has an old house called Bale Tumpang Salu, as well as ancient cultural activities which are still preserved until now, has the potential to develop a virtual tour. In village mentoring activities, tourism awareness groups are given virtual tour training involving the role of the industry, namely the Trex Tour. Through training and mentoring provided by academics and industry, the tourism awareness group of Sidatapa Village was able to design and carry out virtual tours. ==== Kehadiran teknologi informasi yang semakin canggih berimplikasi pada munculnya berbagai inovasi dan kreativitas, dengan memanfaatkan perkembangan dari teknologi informasi tersebut. Salah satu yang sedang berkembang pesat pada masa pandemik adalah virtual tour sebagai pengganti perjalanan wisata ke suatu tempat secara langsung, yang dibawa ke dalam sebuah layar baik menggunakan device berupa laptop, PC, maupun mobile phone. Desa Sidatapa sebagai salah satu desa wisata di Kabupaten Buleleng yang baru saja mengembangkan produk wisata, salah satunya beriwisata mengenal budaya di desa tersebut, mengalami hambatan yang disebabkan oleh pembatasan sosial. Wisatawan tidak dapat berkunjung langsung ke desa tersebut dan mengenal budaya di desa tua tersebut. Melihat tren virtual tour yang berkembang baik di Indonesia maka pada program pengabdian kepada masyarakat ini, kelompok desa wisata yang berperan sebagai pemandu wisata diberikan pelatihan virtual tour. Desa Sidatapa memiliki keunikan, yakni sebagai desa Bali Aga, memiliki rumah tua yang disebut Bale Tumpang Salu, serta aktivitas budaya kuno yang hingga saat ini masih dipertahankan berpotensi untuk mengembangkan virtual tour. Pada kegiatan pendampingan desa, kelompok sadar wisata diberikan pelatihan virtual tour dengan melibatkan peran industri, yakni Trex Tour. Melalui pelatihan dan pendampingan yang diberikan oleh pihak akademisi dan industri, kelompok sadar wisata Desa Sidatapa mampu merancang dan melaksanakan virtual tour.